Finite element method for the static behavior of tapered poles made of glass fiber reinforced polymer. Issue 20 (18th October 2021) - Altanopoulos, Thomas I.; Raftoyiannis, Ioannis G.; Polyzois, Dimos
Abstract: This work addresses the application of the Finite Element Method (FEM) in order to investigate the static behavior of tapered poles made of glass fiber reinforced polymer (GFRP). The theoretical model developed using the FEM was verified through comparison with an experimental procedure. More specifically, two poles made of glass fiber reinforced polymer (GFRP) were loaded as cantilever beams to failure at the Steel Structures Laboratory of the National Technical University of Athens (NTUA). The experimental poles were constructed using the filament winding method. The experimental results included load-deflection data at the point of loading as well as strain distribution near the fixed support. The results from the FEM closely matched the experimental results for deflection as well as for the ultimate load of the specimens. On the basis of these findings, the authors concluded that it is possible to use the FEM with confidence in the analysis and design of GFRP structures, such as utility line poles and wind turbine towers, without the high cost associated with experimentation.